Role of broad ligament in the causation of utrine torsion in dairy buffaloes - BRAR, P S; SAIGAL, R P; NANDA, A S; SHARMA, R D (The Indian Journal of Animal Sciences, 2011)
The present study was carried out on gross structure of broad ligament to ascertain its role in causation of uterine torsion. Gross dissection of broad ligament was done on specimens taken from female buffalo calves born dead, nonpregnant slaughtered buffaloes, buffaloes died following dystocia due to uterine torsion or otherwise and crossbred cows. Broad ligaments of all investigated animals were consisted of double serosal folds with smooth muscle fibres, blood vessels, nerves and connective tissue contained in between them. In cows, muscle fibres had substantial outwards diversification as compared to buffaloes where the fibres primarily run parallel to the genitalia and have fewer outwards diversification. Wide variation in the amount and arrangement of muscles in broad ligament in buffaloes was observed, which has not been reported so far. Broad ligaments in uterine torsion affected buffaloes had thinner muscular development than the dystocia cases. Overall it could be concluded that in buffalo population wide variation exists in broad ligament musculature and a definite proportion has weak broad ligaments, which make them vulnerable to development of uterine torsion. In cows the muscles in broad ligament are better arranged leading to low incidence of uterine torsion in cows.Â